A Systematic Chart Review of Adults with Post-Traumatic Stress Disorder: Data from a Tertiary Care Psychiatry Center in India - K. Krishnakumari; Manjula Munivenkatappa; Shantala Hegde; Kesavan Muralidharan (Indian Journal of Psychological Medicine, 2022)
Background: Post-traumatic stress disorder (PTSD) is an understudied construct in the psychiatric setting. The majority of existing Indian studies on PTSD focus on the general population or disaster-stricken communities. Here, we present data from a five-year retrospective chart review from a tertiary care psychiatric center in India. Methods: Medical records of adult patients (≥18 years) who had attended psychiatry outpatient services between April 1, 2015 and March 31, 2020 (five years) and were diagnosed with PTSD, as per ICD-10 criteria, were reviewed ( n = 113). The relevant sociodemographic and clinical details were extracted using a semistructured pro forma. Results: The percentage of adult patients with PTSD diagnosis in the five years was 0.22%. PTSD was more common in females (n = 65, 57.5%). Most patients had interpersonal trauma (n = 85, 75.2%), specifically sexual abuse (n = 47, 41.6%).The median age of onset was 22 years. All the patients had re-experiencing symptoms, with an equally high rate of avoidance (n = 109, 96.5%) and arousal symptoms (n = 110, 97.3%). 82%(93) had a comorbid psychiatric disorder, with mood disorder being the most common (n = 44, 38.9%). Males had a higher rate of comorbid substance use disorder (n = 14, 29.2%) and depression (n = 20, 42%), and females had a higher rate of comorbid dissociative disorder (n = 13, 20%). Most of the patients received non-trauma-focused psychological interventions, and only 18% (20) received evidence-based trauma-focused psychological interventions. Conclusion: Interpersonal trauma, specifically sexual abuse, largely contributes to PTSD among adults attending psychiatric services. The need for trauma-focused psychological interventions is underscored.